2017
DOI: 10.1007/s11356-017-9822-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil pH and organic matter on the adsorption and desorption of pentachlorophenol

Abstract: Various properties of soil affect the partition of organic contaminants within, and conversely, the properties of the organic contaminants also directly affect their partition behavior in soil. Therefore, understanding the effects of various properties of soil on the partition of organic contaminants favors subsequent assessment and provides soil remediation methods for policymakers. This study selected pentachlorophenol (PCP), a common hydrophobic ionizable organic compound in contaminated sites worldwide, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This may be because soil temperature and humidity increased and promoted the release of N nutrients during the early stages under the plastic film mulching treatments. The alkali-hydrolyzable N content may have subsequently improved and a large concentration of nitric nitrogen led to the decrease of soil pH [34, 35]. The results presented in S3 Table indicate that plastic film mulching treatment had a lower EC than non-plastic film mulching.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because soil temperature and humidity increased and promoted the release of N nutrients during the early stages under the plastic film mulching treatments. The alkali-hydrolyzable N content may have subsequently improved and a large concentration of nitric nitrogen led to the decrease of soil pH [34, 35]. The results presented in S3 Table indicate that plastic film mulching treatment had a lower EC than non-plastic film mulching.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a correlation between pH and microorganisms in bioremediation efficacy. e pentachlorophenol molecules can be biodegraded with the variation of pH and organic matter [28]. ese were confirmed by the soil electrical conductivity measures [29].…”
Section: Discussionmentioning
confidence: 69%
“…The bioavailability and bio-toxicity of pollutants in soils are the main parameters that determine their environmental risk, which can be influenced by various soil factors, like soil pH, redox potential, dissolved organic carbon, microbial community and activities ( Chien et al, 2018 ; Wang et al, 2020 ). Moreover, plant root secretions can also impact the pollutants mobility and transformation in soil and also uptake by, and translocation into, plants ( Lu et al, 2017 ).…”
Section: A New Approach For Assessing the Risk Of Soil Pollution By P...mentioning
confidence: 99%